Effect of nanoclay on the morphology of polyethylene modified bitumen. (30th July 2016) - Mohammadiroudbari, Motahareh; Tavakoli, Akram; Razavi Aghjeh, Mir Karim; Rahi, Mohammad
Highlights: Effect of clay on phase morphology of polyethylene modified bitumen was studied. The clay dispersion was dependent on the content and functionality of polyethylene. The order of mixing influentially affected the phase morphology of polymeric phase. The melting temperature of polyethylene phase in bitumen was decreased. Abstract: The main objective of the present work was to study the effect of nanoclay on the morphology of polyethylene modified bitumen. The bitumen was modified simultaneously with polyethylene and/or maleic anhydride grafted polyethylene and nanoclay in a high shear mixer and characterized by means of morphology and clay dispersion state. The results showed that the state of nanoclay intercalation and/or exfoliation strongly depends on the polymeric phase content, functionality of polyethylene and the mixing procedure of the components. In turn, the dispersion state of the nanoclay influentially affected the phase morphology of swelled polymeric phase. Using functionalized polyethylene and premixing of nanoclay with polyethylene phase led to improved dispersion state of nanoclay in bitumen nanocomposites. Absorption of low molecular bituminous fractions, led to decreased melting temperature of polymeric phase. The presence of nanoclay induced phase separation between polyethylene and functional polyethylene due to higher affinity of nanoclay to functional polyethylene.